POLITIK LUAR NEGERI INDONESIA DAN GLOBALISASI - RENI WINDIANI, RENI WINDIANI (Politika: Jurnal Ilmu Politik, 2010)
AbstrackThe strategy of the implementation of Indonesian Foreign Policy (IFP) is influenced by notonly domestic situation but also by the growth of the international political climate. The rapid changeof the international political climate has to be followed and analyzed continuously in favour of ournational interest. Further more, steps to response those changes have to be decided in theimplementation of IFP in order to reach our national interest.Keywords : Indonesian Foreign Policy, National Interest.